Law on Militia and Self Defense Forces - The National Assembly (2009)
This Law provides for the obligation to join militia and self-defense forces: the organization, tasks and operations of militia and self-defense forces, regimes and policies for militia and self-defense forces and state management esponsibilities for militia and self-defense forces.